Rio Meia Ponte em Goiás: um olhar sobre a sua história e seu valor ambiental(1933 A 2021) - Tavares, Felisberto Rodrigues (2022)
The Meia Ponte river is considered an essential body of water for life in the territory of Goiânia, but historical events related to disordered population growth and industrial growth in the region had the consequences of the installation of several processes of environmental degradation to the Meia Ponte river. In this sense, the research was carried out with the objective of demonstrating the historical, cultural, environmental and economic value of the Meia Ponte River. For this, a bibliographic and documentary rescue was first made about the history of the Meia Ponte River and Goiânia, through a study in the best guides of the research. Next, a cartographic review was made followed by the elaboration of products that illustrate the area of study, using the database of the State Geoinformation System (SIEG), and the Google Earth programs and the free software QGIS version 3.16 to later demonstrate the environmental importance of the Meia Ponte River through its environmental economic value through the Replacement Cost Method (MCR). The study showed that the Meia Ponte River is the main watercourse of the city of Goiânia, even so, it is treated as a problem, often forgotten by the authorities, being only place of eviction. For the Meia Ponte River there have already been some attempts to recover the river in its urban stretch of Goiânia, but most of it without success, however, the studied stretch can be recovered in approximately 15 years, with a cost of R$ 2,783,336.80, and thus, the stocking presents itself with an effective proposal because it puts the river in its proper place, the leading role.